Managing Commodity Price Risk - Hartley, Janet L (Business Expert Press, 2012)
Ebook from IG Library ; Every business is exposed to financial risk stemming from commodity price volatility. Risk exposure may be direct from the prices paid for raw materials transformed into products sold to customers or indirect from higher energy and transportation costs. The purpose of this book is to provide an approach that organizations can implement and adapt for managing commodity price volatility and reducing their exposure to financial risk associated with purchased goods and services. This topic is important for current and future supply chain professionals due to the significant direct financial effects that price volatility has on profitability, organizational cash flow, the ability to competitively price products, new product design, buyer-supplier relationships, and the negotiation process.